PENERAPAN GREEN ACTION DALAM PENGELOLAAN AKOMODASI DI DESA WISATA BAKAS, KECAMATAN BANJARANGKAN KABUPATEN KLUNGKUNG - Susila, I Made Gede Darma; Prayogi, Putu Agus; Sari, Ni Luh Komang Julianthi Paramita (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
In the development of tourism today, the development of accommodation facilities must pay attention to environmental aspects, various environmentally friendly actions are carried out, one of which is green action. Green action is an activity that aims to protect the environment and surrounding communities. The purpose of this study is to analyze the application of green action in accommodation management in Bakas Tourism Village. Descriptive methods with a qualitative approach are used in this study to obtain an overview of the phenomena that occur. The results of this study show that there are several green actions that have been carried out, namely electrical energy efficiency, water use efficiency, and the use of green products. Overall, there has been a good synergy between accommodation managers and tourists who visit, although there are still some obstacles that need to be considered. It is in our common interest to direct tourism development towards quality tourism. It is hoped that in the future the implementation of this green concept can be carried out well considering the benefits provided both in the future.